8.6 The evolution of the vaginal microbiome throughout uncomplicated pregnancy in a UK population. (9th June 2014) - Chandiramani, M; Lee, YS; Kindinger, L; Arulkumaran, S; Marchesi, J; Holmes, E; Nicholson, J; Teoh, TG; MacIntyre, D; Bennett, PR
Abstract : Introduction: The vaginal microbiome plays an important role in maintaining reproductive health throughout pregnancy. Despite the presence of an 'abnormal' vaginal microbial community being associated with an increased risk of preterm birth, interventional trials of antibiotics have failed to demonstrate significant benefit, which is likely due to a poor understanding of the vaginal microbiome in pregnancy. We sought to characterise the vaginal microbiome in uncomplicated pregnancies in a UK-based cohort. Methods: Vaginal swabs were collected at time points across gestation (8–12, 20–22, 28–30 and 34–36 weeks) and the postpartum period (6 weeks) from 43 women delivered at term. Resident bacterial communities were determined using the Illumina MiSeq platform generated from bar-coded amplicons of 16S rRNA gene fragments. Results: Individual vaginal microbiomes in pregnancy fall within four categories; i) Lactobacillus crispatus dominant, ii) Lactobacillus iners dominant, iii) Lactobacillus gasseri mixed with Lactobacillus jensenii and iv) Lactobacillus depleted with a diverse microbiome. Two pregnancy related trends were identified. In one group the Lactobacillus-dominated microbiome remains stable throughout pregnancy whereas in the other, an initially more diverse microbiome in the first trimester becomes Lactobacillus-dominated and less diverse in the second trimester but then reverts back to greater diversity in the third trimester and postpartum. Lactobacillus crispatus was associated with lower diversity and greater stability throughout pregnancy. Conclusion: The vaginal microbiome during pregnancy tends to be Lactobacillus-dominated and less diverse in the period prior to fetal viability. Stability appears to be dependent upon the Lactobacillus species which may have implications for probiotic therapy.